2017
DOI: 10.1017/cem.2017.51
|View full text |Cite
|
Sign up to set email alerts
|

All-terrain vehicle–related injuries and deaths in Newfoundland and Labrador between 2003 and 2013: a retrospective trauma registry review

Abstract: This study describes ATV related injuries and deaths in NL. Information from this study may guide physician practice, public education, and future legislation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
3
2
0
Order By: Relevance
“…24 Differences in the way patients are stratified by age and the age range of patients included in the study affect the estimation of the age group most affected by OHV injuries; however, most studies agree that the highest injury incidence stays between the 10-to 20-year-old age group. 12,14,25 Notably, 8.5% of our patients were 6 years old or younger, which is similar to other studies focusing on pediatric patients consulting to Level I trauma centers, with the percentage of injured patients aged 6 years or younger ranging from 5% to 11%. 21,26,27 The impact of age on accident severity showed that children 6 and younger have lower PTS scores which are related to higher mortality.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…24 Differences in the way patients are stratified by age and the age range of patients included in the study affect the estimation of the age group most affected by OHV injuries; however, most studies agree that the highest injury incidence stays between the 10-to 20-year-old age group. 12,14,25 Notably, 8.5% of our patients were 6 years old or younger, which is similar to other studies focusing on pediatric patients consulting to Level I trauma centers, with the percentage of injured patients aged 6 years or younger ranging from 5% to 11%. 21,26,27 The impact of age on accident severity showed that children 6 and younger have lower PTS scores which are related to higher mortality.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the US trends demonstrated by a study using the National Electronic Injury Surveillance System database, the 14- to 17-year-old age group is 2.8 times more likely to suffer an ATV injury among both children and adults 24 . Differences in the way patients are stratified by age and the age range of patients included in the study affect the estimation of the age group most affected by OHV injuries; however, most studies agree that the highest injury incidence stays between the 10- to 20-year-old age group 12,14,25 . Notably, 8.5% of our patients were 6 years old or younger, which is similar to other studies focusing on pediatric patients consulting to Level I trauma centers, with the percentage of injured patients aged 6 years or younger ranging from 5% to 11% 21,26,27 …”
Section: Discussionsupporting
confidence: 84%
“…We found that helmet use among ORV crashes was just under 50% and that alcohol use decreased the likelihood of helmet use. A study from Newfoundland and Labrador reported similar results in their local study population [20].…”
Section: Comparison To Previous Studiessupporting
confidence: 52%
“…12 Previous studies have described poor rates of helmet use in ATV-related events, with one study suggesting only a 48.7% rate of usage in pediatric ATV accidents. 5 Additionally, ATV accidents mapped in the state of Iowa revealed that helmet use in the rural setting was statistically lower than in the urban setting. 9 Our study reaffirms the utility of helmets and the continued need for its promotion among this unique patient population.…”
Section: Discussionmentioning
confidence: 99%
“…3 While some policy suggestions made by the AAP have prompted changes in state legislation, their effects on limiting morbidity have been unclear. Data from Nova Scotia, 4 Newfoundland and Labrador, 5 Canada have suggested that legislation may be was ineffective in decreasing ATV-related injury. Additionally, cost analysis data reported by Strohecker et al suggest that the use of helmets, advocated by the AAP, only slightly shortened hospital length of stay.…”
Section: Introductionmentioning
confidence: 99%